Critical Analysis of Paramedic and Nursing Roles in Disaster Management in Strengthening Rapid Response and Community Resilience - Alotaibi, Mohammed Meshal; Aljuaid, Adel Mater; Alshammari, Sulaiman Fayed; Alghamdi, Waleed Mohammed; Alnefaie, Faisal Saeed; Alnefaie, Nawaf Saeed; Althuwaylimi, Anas Abdullatif; Najjar, Roaa Ahmed Bakr; Hassan, Hassan Mashawi; Alharthi, Mohammed Salem (Journal of Ecohumanism, 2024)
Disaster management plays a significant role in the provision of response, rescue, and care for populations during disasters, and paramedics and nurses contribute enormously to increasing the speed of the disaster. Therefore, this paper aims to discuss the roles of paramedics and nurses before, during, and after disasters, as well as in disaster planning. This paper comprehensively discusses challenges and prospects likely to be encountered by paramedics and nurses during disasters, focusing on interdisciplinary coordination, training, and resource management, based on a critical analysis of existing literature. This study shows that it is possible to increase the efficiency of disaster response and improve the population’s ability to survive when paramedics and nurses are employed in management networks. However, some concerns remain about training, coordination, and resource management. The suggestions are to enhance collaboration between the treatment teams, allocate resources in the programs focused on enhancing disaster response skills, and establish guidelines that would guarantee a strong healthcare reaction to calamities.